A Survey On The Level Of Recognition Of Intellectual Capital - Kin, Gan (2001)
The study was conducted using questionnaires with the aim of surveying the level of recognition/awareness of intellectual capital among managers in the financial services and high-technology manufacturing industries in Melaka.